Effect of Activated Carbon Made from Cocoa (Theobroma Cacao L.) Shells on the Adsorption of Iron in Aquifer Water - Azabache Liza, Yrwin F. (2022)
This research aims to determine the effect of activated carbon obtained from cocoa husks (Theobroma cacao L.) on the adsorption of iron (II) present in water of an aquifer for human consumption. Charcoal was prepared at different carbonization temperatures (500, 600 and 700 °C) for 30 minutes and activated with phosphoric acid in the proportions of 1:1. Iron (II) adsorption was determined as a function of variations in mixing speed, contact time, charcoal dosage and stirring speed. It was determined that, over the range considered, agitation speeds had no significant effect on the percentage of iron (II) removal, being the dose of activated carbon and temperature, the most influential variables. The water samples had an initial iron concentration of 3.15 mg/L and 4 mg/L. The best iron (II) adsorption result was obtained with activated carbon at the carbonization temperature of 700 °C, with a mass of 1.5 g of carbon, with efficiencies of 93 % and 98 % for both samples considered. Based on the results, it was concluded water for human consumption is treatable with activated carbon derived from Theobroma cacao L. for the adsorption of iron (II), considering that this parameter is below the maximum limit of 0.3 mg/L allowed by current regulations.